Conservação in situ de indivíduos de Pityrocarpa moniliformis (Benth.) Luckow & R. W. Jobson para seleção de árvores matrizes - Felix, Francival Cardoso (2019)
Pityrocarpa moniliformis (Benth.) Luckow & RW Jobson (Fabaceae) is an arboreal species that possesses ecological, social and economic potential for Northeastern Brazil, with several wood and non-timber uses, thus highlighting the importance of this species to the conservation and development of semiarid regions. The objective of this work was to select P. moniliformis matrices trees for seed production and in situ conservation, evaluating the genetic diversity with the use of molecular markers Inter Simple Sequence Repeat (ISSR), and seed biometry through digital image processing for studies of genetic divergence, as well as physical, sanitary and physiological quality evaluation of seeds of different trees. The work was divided into three stages, each of which is described in chapter form. In Chapter 01, 28 ISSR molecular markers were tested, evaluating the total number of loci, polymorphism rate and content value of the polymorphic information (PIC). Seven primers were selected for genetic diversity studies of P. moniliformis, which provided 74 loci, 82% polymorphism and PIC of 0.344. In Chapter 02, seed biometrics of 33 lots were performed by means of digital image processing, with descriptive statistics analysis, main components, and correlation between Euclidean distance and genetic similarity of trees with the use of molecular markers ISSR. The digital image processing was efficient in detecting biometric differences in batch seed, which has a variation of morphological and biometric aspects due to genetic differences among P. moniliformis trees. In chapter 03, seeds of 44 trees were submitted to quality determination and genetic diversity for matrices and progenies. About 80 and 40% of the trees produced seeds with germination higher than 50 and 70%, respectively. The P. moniliformis trees produce seeds with different levels of quality, being selected as trees producing seeds of high and medium physiological quality, eleven and fifteen matrices, respectively. The selected progenies represent 64% of the source of total variation in the loci, and only 36% are due to variation between matrices.